2013
DOI: 10.1155/2013/782137
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Carotenoids and Their Antioxidant and Anti-Inflammatory Effects in Cardiovascular Care

Abstract: Cardiovascular disease related to atherosclerosis represents nowadays the largest cause of morbidity and mortality in developed countries. Due to inflammatory nature of atherosclerosis, several studies had been conducted in order to search for substances with anti-inflammatory activity on arterial walls, able to exert beneficial roles on health. Researches investigated the role of dietary carotenoids supplementation on cardiovascular disease, due to their free radicals scavenger properties and their skills in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(178 citation statements)
references
References 99 publications
4
165
0
3
Order By: Relevance
“…Some of the carotenes can be converted into vitamin A in the human body. Previous research findings showed that the foods enriched with carotenoids possessed various protective health benefits such as anti-inflammatory, antioxidant and anticancer activities 31 . An increase in the consumption of carotenoids-rich food are claimed to be 33 .…”
Section: Total Sterol Carotene and Squalene Contentsmentioning
confidence: 99%
“…Some of the carotenes can be converted into vitamin A in the human body. Previous research findings showed that the foods enriched with carotenoids possessed various protective health benefits such as anti-inflammatory, antioxidant and anticancer activities 31 . An increase in the consumption of carotenoids-rich food are claimed to be 33 .…”
Section: Total Sterol Carotene and Squalene Contentsmentioning
confidence: 99%
“…Among patients with chronic kidney disease (CKD), OS increases in correlation with renal dysfunction [4], and enhanced OS among CKD patients induces an increase of CVD mortality and morbidity [5]. Such OS is widely considered as therapeutic target [6].…”
Section: Introductionmentioning
confidence: 99%
“…They protect human body against cardiovascular disease, arteriosclerosis and cancer (Ciccone et al, 2013;Relevy et al, 2015).…”
Section: Resultsmentioning
confidence: 99%